A two-factor theoretical model of social media discontinuance: role of regret, inertia, and their antecedents. Issue 1 (24th June 2020) - Wang, Junkai; Zheng, Bowen; Liu, Hefu; Yu, Lingling
Abstract : Purpose: Although materializing the benefits of social media substantially depends on sustained user participation, social media service providers are experiencing a decline in the number of users. Despite the relevance of studying and managing discontinuance behaviors, a systematic empirical investigation remains lacking. The present study draws on the idea of a two-factor model and aims to examine the enabler, inhibitor and their antecedents in the context of social media discontinuance. Design/methodology/approach: The proposed theoretical model was empirically validated through an online survey study of 238 social media users in China. Findings: Findings indicated that two negative outcomes of social media use (i.e. social overload and invasion of privacy) induce regret experience and ultimately foster discontinuance intentions. The development of discontinuance intentions was undermined by the level of inertia, which is rooted in social media habit, sunk costs and affective commitment. Originality/value: This study draws attention to the fundamental difference between continuance and discontinuance behaviors, advances the existing understanding of postadoption behaviors by focusing on discontinuance inhibitors (e.g. inertia) and develops the first two-factor model for social media discontinuance by integrating the regret and status quo bias literature.